A Versatile Iron-Tannin-Framework Ink Coating Strategy to Fabricate Biomass-Derived Iron Carbide/Fe-N-Carbon Catalysts for Efficient Oxygen Reduction - Wei, J.; Liang, Y.; Hu, Y.; Kong, B.; Simon, G.; Zhang, J.; Jiang, San Ping; Wang, H. (2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. The conversion of biomass into valuable carbon composites as efficient non-precious metal oxygen-reduction electrocatalysts is attractive for the development of commercially viable polymer electrolyte membrane fuel-cell technology. Herein, a versatile iron-tannin-framework ink coating strategy is developed to fabricate cellulose-derived Fe3C/Fe-N-C catalysts using commercial filter paper, tissue, or cotton as a carbon source, an iron-tannin framework as an iron source, and dicyandiamide as a nitrogen source. The oxygen reduction performance of the resultant Fe3C/Fe-N-C catalysts shows a high onset potential (i.e. 0.98 V vs the reversible hydrogen electrode (RHE)), and large kinetic current density normalized to both geometric electrode area and mass of catalysts (6.4 mAcm-2 and 32 mAmg-1 at 0.80 V vs RHE) in alkaline condition. This method can even be used to prepare efficient catalysts using waste carbon sources, such as used polyurethane foam.